2015
DOI: 10.1590/s1677-5538.ibju.2014.0348
|View full text |Cite
|
Sign up to set email alerts
|

Beyond biology: the impact of marital status on survival of patients with adrenocortical carcinoma

Abstract: Purpose:To analyze the association of marital status and survival of patients with ACC using a population-based database.Material and Methods:Patients with ACC were abstracted from the Surveillance Epidemiology and End Results (SEER) database from 1988-2010 (n=1271). Variables included marital status (married vs single/divorced/widowed (SDW)), gender, age, race, tumor (T) and node (N) classification, receipt of surgery, and SEER stage. Statistical analysis was performed using Cox proportional hazard models to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Our finding showed that married group had higher survival rate in patients of TNM stage I, II and IV. Although this correlation between marriage and cancer was supported by previous studies 18 22 , the reasons were not fully understood. Unlike unmarried ones, married patients are more likely to receive standard treatments and social support.…”
Section: Discussionmentioning
confidence: 52%
“…Our finding showed that married group had higher survival rate in patients of TNM stage I, II and IV. Although this correlation between marriage and cancer was supported by previous studies 18 22 , the reasons were not fully understood. Unlike unmarried ones, married patients are more likely to receive standard treatments and social support.…”
Section: Discussionmentioning
confidence: 52%
“…However, the study also found patient experiences and partner perspectives influences wellbeing. The effect of a supportive partner was identified by another study which found marital status had positive association ( p = .008) with ACC survival 39 . It has been suggested that this might be attributed by increased peer support for access to healthcare, treatment adherence and willingness to seek help.…”
Section: Discussionmentioning
confidence: 94%
“…The effect of a supportive partner was identified by another study which found marital status had positive association ( p = .008) with ACC survival. 39 It has been suggested that this might be attributed by increased peer support for access to healthcare, treatment adherence and willingness to seek help. These findings align with the themes in our systematic review and reinforce the case for qualitative research in people with AI/ACC.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with earlier research that showed metastatic disease and a more advanced stage to be independent predictive factors for OS and CSS ( Ayala-Ramirez et al, 2013 ). Zachary Klaassen showed that single, divorced, or widowed (SDW) patients have much higher cancer-specific death rates than married patients ( Klaassen et al, 2015 ). However, in our study, marital status was not related to survival in ACC patients.…”
Section: Discussionmentioning
confidence: 99%